Use of Online Shop in Instagram in Women's Consumptive Behavior in Jakarta - Fauziah Fauziah (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The rise of shopping through online stores on Instagram makes women in Jakarta a problem in this case. Generally women do online shopping not only on the mere needs, for the sake of and the lifestyle of a country called wasteful or better known as consumptive behavior or consumerism behavior. This study used qualitative research methods. The results of research conducted on six people obtained information from online consumer behavior in Jakarta has entered the consumer category or online shopping on large Instagram for women, online shopping or online stores are more interested in shopping problems with reasons and behavior because they are not want to miss the trend and offer prices from online stores even though the product is not needed.